PERTUMBUHAN ASET, PROFITABILITAS DAN RASIO AKTIVITAS DALAM MEMPREDIKSI BETA SAHAM PERUSAHAAN MANUFAKTUR DI INDONESIA - Hidayat, Riskin; Fauziah, Uji Lutfi; Sari, Dian Anita (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2021)
This study aims to test profitability, activity ratios, and asset growth in predicting stock betas in manufacturing firms listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling and obtained a sample of 49 firms with a total of 245 observations. Data obtained from the Indonesia Stock Exchange. Data analysis used multiple linear regression. The results showed that asset growth had a significant negative influence on stock beta, profitability as proxied by return on equity and activity ratio proxied by total asset turnover had an insignificant negative influence on stock beta. The results of the determination test show that 23.6% of the stock beta variable can be explained by variations of the independent variables and the remaining 76.4% is explained by other causes outside the model in this study